Medical Nutrition Therapy in Short Bowel Syndrome and Food Interventions in Intestinal Adaptation - Ebru KOPTAGEL; Hülya KAMARLI ALTUN (Atatürk University, 2021)
The 'normal' length of the small intestine ranges from 320 to 800 cm. short bowel syndrome is defined as the small bowel length less than 200 cm. Short bowel syndrome is a clinical manifestation that occurs mainly after anatomical and / or functional loss of small intestine and presents with diarrhea, steatorrhea, weight loss, malnutrition, malabsorption, dehydration. Therefore, appropriate nutritional therapy should be planned, and lost fluid and electrolytes should be replaced. A nutritional plan should be drawn up considering other factors affecting the disease and the type of surgical procedure. The main goal of treatment in short bowel syndrome is to achieve bowel adaptation. Nutritional interventions such as glutamine, growth hormone, fish oil and probiotics-prebiotics have recently been investigated for intestinal adaptation. The aim of this review is to examine medical nutrition therapy in short bowel syndrome and nutritional interventions in bowel adaptation.